Innovative Tools of Educational Organization Development Management: Benchmarking - E. O. Okunkova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article considers theoretical and methodological approaches to the use of benchmarking as an innovative tool in the management of an educational organization. The development of methods and tools for managing the development and competitiveness of an educational organization in the global space is based on systemic, operational, competent and situational methodological approaches; on the methodology of interactive, understanding and interpretative sociology; methodologies of synergy, network thinking and social management, modal analysis. The study found that benchmarking is the most appropriate way to improve the work of the educational organization, which is a process of constantly measuring and comparing the methods and results of the work of the organization, its individual divisions, functions, processes with organizations chosen for imitation. The author presents the results of the study of the forms of benchmarking, conducted a review of research on its application by educational organizations of higher education in Russia, presented a detailed analysis of the main stages of its implementation in relation to the specifics of the activities of the educational organization, visualized a set of types of benchmarking by classification groups.